Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

Interfacial engineering enables in-situ growth of MIL-88A(Fe) on PVDF membranes for high-performance ultrafiltration: Breaking the permeability-selectivity trade-off and enhancing fouling/oxidation resistance - Ziyu Jia; Miao Chang; Xiaoyue Zhang; Zhi-Bo Wang; Hong-Yu Chu; Zhihao Shi; Ruo-Xuan Mei; Chong-Chen Wang; Peng Wang; Anping Wang; Jiguang Deng (Water Research, 2026)

SNX8 interacts with THOC7 to negatively regulate IFN 1 response via the TBK1-IRF3 signaling axis in teleost fish - Miao-miao Li; Chu-xin Wu; Ji-huan Hu; Ting-ting Yu; Ze-yin Jiang; Hong-ying Zhang; Xun-hang Li; Cheng-yu Hu (Fish & Shellfish Immunology, 2026)

Multifunctional IB metal-doped SWCNT films with ultralow thermal conductivity and electron–phonon decoupling for wearable thermoelectric - Tong-Yu Li; Wen-Hao Geng; Yue-Xin Wang; Chu-dan Wang; Wenyi Wang; Qingxia Zhu; Di Zhang; Xuguo Huai; Hong-Zhang Geng (Chemical Engineering Journal, 2026)

Hydrogen-bond-polarized iodine capture: Enhanced uptake in humid exhaust streams by a plant-based Zr-MOF - Lu-Hao Xu; Lu Zhang; Yu-Meng Sun; Hong-Yu Chu; Chong-Chen Wang; Anping Wang; Peng Wang; Xiao-Hong Yi; Jiguang Deng (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Low enthalpy 3D evaporators coupled with auxiliary thermal management for rapid solar evaporation - Ze-Ming Huang; Hong-Yu Chu; Ye-Tong Liu; Xiang-Jing Mo; Jing Li; Chong-Chen Wang; Peng Wang; Xiao-Hong Yi (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Localized surface plasmon resonance-enhanced photocatalytic valorization of biomass to biodegradable plastic precursors - Longfei Hong; Liangdong Hu; Lianhua Xu; Qingyu Liu; Xiang Gao; Jiajun Yu; Sheng Chu; Huiyan Zhang (Chemical Engineering Journal, 2026)

Deciphering the different Mycobacterium avium complex infections of HIV and non-HIV patients by bacterial GWAS and immune cells flow cytometry - Yue Hou; Hong Sun; Shuang Meng; Wenzhao Xu; Yanhua Yu; Wenjing Wang; Dingyi Liu; Hongbing Jia; Yajie Wang; Hongqian Chu; Zhaogang Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Ecological roles of lactic acid bacteria biodiversity and cross-feeding in shaping the flavor landscape of traditional Huangjiu fermentation - Chao-Jie Zhu; Yi-Ling Zhong; Yong-Zhu Zhang; Zhi-Chu Shan; Hong-Yan Qu; Fei Cheng; Wei Feng; Peng Wang; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Bioresource Technology, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Fixed-bed catalytic antibiotics detoxification through singlet oxygen-mediated nonradical oxidation: Mechanisms and long-term performance - Guang-Chi Liu; Xing-Yuan Liu; Xiao-Hong Yi; Fei Wang; Hong-Yu Chu; Xiao-Hang Xu; Yi-Meng Zhou; Peng Wang; Jian-Feng Wang; Chong-Chen Wang (Water Research, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Effects of curcumin and Curcuma longa extract on inflammatory biomarkers in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE): a systematic review and meta-analysis of randomized controlled trials - Ang-Jun Liu; Po-Chang Wu; Yu-Pei Chen; Hsueh-Ting Chu; Hen-Hong Chang (Inflammation Research, 2025)

Myostatin b gene-edited mutation on Streptococcus resistance, innate immunity and lipid metabolism in Nile tilapia - Ting-Yu Huang; Chong-An Zeng; Wai-Kwan Chu; Yu-Ting Huang; Chang-Wen Huang; Jen-Leih Wu; Hong-Yi Gong (Fish & Shellfish Immunology, 2025)

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Advancing closed-loop plastic economy: Mechanochemical synthesis of MIL-53(Fe)@PET (PSM-53) from waste plastics for sustainable antibiotic remediation - Chao-Yang Wang; Chong-Chen Wang; Hong-Yu Chu; Peng Wang (Science of The Total Environment, 2025)

Tough, adhesive, and conductive hydrogels enabled by stabilized PEDOT/sulfated cellulose dispersions for extreme-temperature sensing - Xiaowen Xie; Sirui Sun; Hong Wang; Yuezhen Hua; Zenghui Cheng; Juan Yu; Tongqi Yuan; Chunpeng Wang; Fuxiang Chu; Jifu Wang (Chemical Engineering Journal, 2025)

Insight into the control of hydrogen sulfide release in anaerobic reactor treating sulfate-laden wastewater: Multivariate effects and microbial competition - Biaojun Zhang; Yao Lu; Weilin Wu; Wona Ding; Hong Yu; Hui Chen; Bei Chu; Shaobin Huang (Journal of Environmental Chemical Engineering, 2025)

The phenylalanine synthesized by whitefly–Portiera symbiosis enhances host survival under fungi infection - Chao Lv; Song-Xue Zhang; Ji-Sheng Hong; Tian-Yu Wang; Bing-Qi Liu; Chu-Qiao Li; Jin-Yang Yan; Jun-Bo Luan (Journal of Pest Science, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Jatrophane and ingenane diterpenoids with anti-inflammatory activity from Euphorbia esula - Yu-Peng Li; Ying Li; Wen-Jing Gao; Chu-Hong Fang; Ming-Jun Lv; Jian-Min Yue; Jin-Hai Yu (Phytochemistry, 2025)

Global-scale geo-evolutionary feedbacks: a tale by oxygen - Xin-Yi Chu; Hong-Yu Zhang (Trends in Ecology & Evolution, 2025)

Paleoproterozoic granite in the Khondalite Belt, northern margin of the North China Craton: Response to the assembly of the Columbia supercontinent - Qiang Shi; Run-Xiao Shu; Xiang-Zhi Chen; Guo-Chun Zhao; Yu-Song Chen; Zhao-Sheng Wang; Long Ma; Zhong-Yuan Xu; Zheng-Hong Liu; Kai-Yun Chen; Hui-Chu Wang (Precambrian Research, 2025)

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

Deferoxamine-induced neurotoxicity: Role of chaperone-mediated autophagy dysfunction in neuronal apoptosis in the hippocampus - Hong Zhang; Jian Guo; Jiayi Chu; Huanhuan Yu; Jialin Zhang; Siman Ma; Ge Jin; Yingshan Jiang; Jiao Xiao; Yutong Hou; Minyan Li; Shiliang Yin (Chemico-Biological Interactions, 2025)

Impact of photoaging on the chemical and cytotoxic properties of nanoscale zeolitic imidazolate framework-8 - Yi-Chun Chen; Kun-Yi Andrew Lin; Ying-Chu Chen; Yan-Yu Hong; Yu-Fang Hsu; Chia-Hua Lin (Journal of Hazardous Materials, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Associations between exposure to brominated flame retardants and periodontitis in U.S. adults - Jia-jie Lv; Shu-yue Li; Xiang-meng Kong; Yan Zhao; Xin-yu Li; Hong Guo; Chu Feng; Cheng-hao Yang (Chemosphere, 2024)

Analysis of flavor substances changes during fermentation of Chinese spicy cabbage based on GC-IMS and PCA - Wenkui Guo; Meiru Cheng; Xuemei Dong; Chuan Liu; Yu Miao; Peng Du; Hong Chu; Chun Li; Libo Liu (Food Research International, 2024)

Floating MIL-88A(Fe)@expanded perlites catalyst for continuous photo-Fenton degradation toward tetracyclines under artificial light and real solar light - Guang-Chi Liu; Xiao-Hong Yi; Hong-Yu Chu; Chong-Chen Wang; Ya Gao; Fei Wang; Fu-Xue Wang; Peng Wang; Jian-Feng Wang (Journal of Hazardous Materials, 2024)

Prussian blue analogue nanospheres immobilized on self-floating biochar for micropollutant degradation via photo-Fenton process - Fu-Xue Wang; Zi-Wei Zhang; Zi-Chen Zhang; Ke-Xin Li; Ya Li; Hong-Yu Chu; Chong-Chen Wang; Jian-Feng Wang; Long Chen; Wen Liu; Hailong Wang; Peng Wang (Chemical Engineering Journal, 2024)

Efficient EVs separation and detection by an alumina-nanochannel-array-membrane integrated microfluidic chip and an antibody barcode biochip - Jiaoyan Qiu; Qindong Guo; Yujin Chu; Chunhua Wang; Hao Xue; Yu Zhang; Hong Liu; Gang Li; Lin Han (Analytica Chimica Acta, 2024)

Novel modified semi-carbonized fiber prepared using discarded clothes for derisking Cu(II) and Pb(II) contaminated water - Hong-yan Deng; Yin-fei Wang; Meng-ting Guo; Wen-bin Li; Min Li; Chu-tong Yu (Journal of Environmental Management, 2024)

Aerobic Glycolysis Induced by mTOR/HIF-1α Promotes Early Brain Injury After Subarachnoid Hemorrhage via Activating M1 Microglia - Xin-Gang Sun; Xue-Hong Chu; Ivan Steve Godje Godje; Shao-Yu Liu; Hui-Yu Hu; Yi-Bo Zhang; Li-Juan Zhu; Hai Wang; Chen Sui; Juan Huang; Ying-Jie Shen (Translational Stroke Research, 2024)

O-acetyl-homoserine sulfhydrylase deficient Streptococcus suis serotype 2 strain SC19 becomes an avirulent strain and provides immune protection against homotype infection in mice - Tong Wu; Hexiang Jiang; Fengyang Li; Xuan Jiang; Jun Wang; Shaopeng Wei; Yi Sun; Yanyan Tian; Hong Chu; Yu Shi; Nan Zhang; Na Li; et al. (Veterinary Microbiology, 2024)

The potential role of subseafloor fungi in driving the biogeochemical cycle of nitrogen under anaerobic conditions - Jun-Peng Jiang; Shuang Leng; Yi-Fan Liao; Xuan Liu; Dong-Xu Li; Chen Chu; Xiang-Yang Yu; Chang-Hong Liu (Science of The Total Environment, 2023)

Mid-Holocene pine forest expansion caused by the weakening of the East Asian winter monsoon and linked to climate change in the North Atlantic region - Jing Wu; Wei-he Ren; Qiao-yu Cui; Yu-zhen Ma; Laurent Marquer; Hong-wei Meng; Ze-yang Zhu; Guo-qiang Chu; Jia-qi Liu (Quaternary Science Reviews, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Triterpenoids with multi-skeletons as 11 β -HSD1 inhibitors from Euphorbia sikkimensis - Chu-Hong Fang; Yu-Peng Li; Ying Li; Jian-Min Yue; Jie Bao; Jin-Hai Yu (Phytochemistry, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Insights on the stem elongation of spur-type bud sport mutant of ‘Red Delicious’ apple - Wen-Fang Li; Zong-Huan Ma; Zhi-Gang Guo; Cun-Wu Zuo; Ming-Yu Chu; Juan Mao; Bai-Hong Chen (Planta, 2023)

Peroxymonosulfate activation for effective atrazine degradation over a 3D cobalt-MOF: Performance and mechanism - Ya Li; Fei Wang; Xueying Ren; Peng Wang; Fu-Xue Wang; Hong-Yu Chu; Shijie Gao; Chong-Chen Wang (Journal of Environmental Chemical Engineering, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

MdbHLH51 plays a positive role in anthocyanin accumulation in ‘Red Delicious’ apples - Gai-Xing Ning; Wen-Fang Li; Ming-Yu Chu; Zong-Huan Ma; Ping Wang; Juan Mao; Bai-Hong Chen (Trees, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Effects of Microplastics on Reproduction and Growth of Freshwater Live Feeds Daphnia magna - Chih-Hsiung Huang; Tah-Wei Chu; Chiu-Hui Kuo; Ming-Chang Hong; Yu-Yun Chen; Bonien Chen (Fishes, 2022)
In recent years, much research has focused on studying the damage caused by microplastics to the ecological environment and human health. Indeed, MPs are often consumed by shellfishes and zooplanktons due to their similarity in size to POM (particular organic matter). Especially in zooplankton, the accumulation of MPs in the body affects the reproductive system and the growth rate of juveniles. Moreover, toxins derived from MPs are continuously accumulated in predators of zooplankton and impact the whole ecosystem across the food chain. In this work, we found that even though MPs were internalized by and adherent around Daphnia magna, there were no significant differences in the survival rate of their adults and offspring. However, the population of ovigerous adults under high MPs exposure for 7 days decreased significantly, suggesting an extension of the days of sexual maturity in D. magna. The removal of MPs after 7 days’ MPs treatment resulted in an increase in D. magna juveniles and neonates which indicated their growth was reduced or inhibited in the MPs environment. Overall, the uptake of MPs led to negative effects on population reproduction and the growth of offspring in D. magna.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

Petrogenesis of two types of gabbro from Neoproterozoic Fuchuan ophiolite complex, Jiangnan Orogen: Implication for a Japan Sea‐like back‐arc basin - Wentao Hong; Minggang Yu; Zhentao Song; Pingli Chu; Kai Liu; Xiaohua Zhou (Island Arc, 2022)
The Neoproterozoic Fuchuan ophiolite complex (FCO) represents the lithospheric remnant of the back‐arc basin in the southeastern margin of the Yangtze Craton. However, the nature and development of this back‐arc system are still confusing. This study focuses on the tholeiitic gabbros in the FCO, which can be divided into enriched and depleted types according to their geochemical characteristics. Enriched gabbros (843 ± 5 Ma) in the FCO are characterized by left‐sloping rare earth element (REE) patterns and relatively low ε Hf (t) (mostly in the range of 4.6–7.8). In contrast, depleted gabbros are slightly younger (838 ± 5 Ma) and isotopically more depleted (ε Hf (t) mostly in 7.7–11.8) than enriched gabbros, exhibiting flat REE patterns. Based on geochemical variations and numerical modeling, the primary magmas of enriched gabbros were generated by a low degree (~14 %) partial melting of the melt‐modified depleted mantle. In contrast, the more depleted isotopic composition and variable Ba/Th and V/Yb ratios of depleted gabbros suggest that their magmas have originated from a higher degree (~14–26 %) partial melting of the fluid‐modified residual depleted mantle. Considering that the most ~860–830 Ma magmatism in the eastern Jiangnan Orogen is calc‐alkaline, the Neoproterozoic back‐arc basin where the FCO formed could be sialic and built on the thinning continental crust, resembling the Japan Sea. The occurrences of tholeiitic gabbros in the FCO thus provide crucial insights into the opening of the back‐arc basin in the southeastern margin of the Yangtze Craton. The changes of mantle source nature and metasomatic agent reflect the upwelling of the depleted asthenosphere and oceanward retreading of the continental arc during the back‐arc opening. Consequently, the early continental arc in the southeastern Yangtze Craton may have been transformed into a new island arc, resembling the formation of the northeast Honshu arc during the Miocene.

Application of Plant Print Identification Technology in Salt-resistant Soybean Breeding - Yan Li; Xia Li; Zi-qi Chen; Ying Ma; Guang-yu Yang; Ying Zhang; Ming-chun Sun; Li-hong Zhang; Jin-meng Chu; Jing-mei Lu; Jun Zhu; Ji-hong You (Journal of Plant Growth Regulation, 2021)

Steroidal glycosides from the underground parts of Hosta ventricosa and their anti-inflammatory activities in mice - Hong-Biao Chu; Nan-Nan Li; Zong-Ping Zhang; Xiao-Yue Hu; Cai-Yun Yu; Lei Hua (Natural Product Research, 2021)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

The m6A methyltransferase METTL3 cooperates with demethylase ALKBH5 to regulate osteogenic differentiation through NF-κB signaling - Jinjin Yu; Lujun Shen; Yanli Liu; Hong Ming; Xinxing Zhu; Maoping Chu; Juntang Lin (Molecular and Cellular Biochemistry, 2020)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Physiological Concentration of Prostaglandin E2 Exerts Anti-inflammatory Effects by Inhibiting Microglial Production of Superoxide Through a Novel Pathway - Shih-Heng Chen; Yueh-Feng Sung; Esteban A. Oyarzabal; Yu-Mei Tan; Jeremy Leonard; Mingri Guo; Shuo Li; Qingshan Wang; Chun-Hsien Chu; Shiou-Lan Chen; Ru-Band Lu; Jau-Shyong Hong (Molecular Neurobiology, 2018)

Activating adenosine A1 receptor accelerates PC12 cell injury via ADORA1/PKC/KATP pathway after intermittent hypoxia exposure - Hong-Fang Mei; Neha Poonit; Yi-Chun Zhang; Chu-Yuan Ye; Hui-Lin Cai; Chen-Yi Yu; Yong-Hai Zhou; Bei-bei Wu; Jun Cai; Xiao-Hong Cai (Molecular and Cellular Biochemistry, 2018)

Association between short-term exposure to ambient air pollution and daily mortality: a time-series study in Eastern China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Effects of air pollution on hospital visits for pneumonia in children: a two-year analysis from China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Mutations in Ralstonia solanacearum loci involved in lipopolysaccharide biogenesis, phospholipid trafficking and peptidoglycan recycling render bacteriophage infection - Yu-Hau Hong; Chi Huang; Kuan-Chung Wang; Tai-Hsiang Chu; Chien-Hui Li; Yu-Ju Chu; Chiu-Ping Cheng (Archives of Microbiology, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Geochronological and geochemical constraints on the Erguna massif basement, NE China – subduction history of the Mongol–Okhotsk oceanic crust - De-You Sun; Jun Gou; Tian-Hao Wang; Yun-Sheng Ren; Yong-Jiang Liu; Hong-Yu Guo; Xiao-Ming Liu; Zhao-Chu Hu (International Geology Review, 2013)

Photochemical degradation of ciprofloxacin in UV and UV/H2O2 process: kinetics, parameters, and products - Hong-Guang Guo; Nai-Yun Gao; Wen-Hai Chu; Lei Li; Yong-Ji Zhang; Jin-Shan Gu; Yu-Liang Gu (Environmental Science and Pollution Research, 2013)

Destrin deletion enhances the bone loss in hindlimb suspended mice - Feng Shuang; Yu Sun; Huai-He Yang; Yin-Chu Shao; Hao Li; Wei Hu; Jun Zhong; Hong-Xing Zou (European Journal of Applied Physiology, 2013)

Dextromethorphan Attenuated Inflammation and Combined Opioid Use in Humans Undergoing Methadone Maintenance Treatment - Shiou-Lan Chen; Sheng-Yu Lee; Pao-Luh Tao; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsien Chu; Po See Chen; I Hui Lee; Tzung Lieh Yeh; Yen Kuang Yang; Jau-Shyong Hong; Ru-Band Lu (Journal of Neuroimmune Pharmacology, 2012)

Erratum to: Inflammation in Patients with Schizophrenia: The Therapeutic Benefits of Risperidone Plus Add-On Dextromethorphan - Shiou-Lan Chen; Sheng-Yu Lee; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsieh Chu; Nian-Sheng Tzeng; I-Hui Lee; Po-See Chen; Tzung Lieh Yeh; San-Yuan Huang; Yen-Kuang Yang; Ru-Band Lu; et al. (Journal of Neuroimmune Pharmacology, 2012)

Potential involvement of CCL23 in atherosclerotic lesion formation/progression by the enhancement of chemotaxis, adhesion molecule expression, and MMP-2 release from monocytes - Chu-Sook Kim; Ji-Hye Kang; Hong-Rae Cho; Thomas N. Blankenship; Kent L. Erickson; Teruo Kawada; Rina Yu (Inflammation Research, 2011)

Two novel single nucleotide polymorphisms (SNPs) and 4-bp deletion mutation of RBP4 gene in Chinese cattle - Mou Wang; Xinsheng Lai; Hui Yu; Juqiang Wang; Zhong-Qi Chen; Xian-Yong Lan; Chu-Zhao Lei; Hong Chen (Journal of Genetics, 2010)

Effects of oral Lactobacillus plantarum on hepatocyte tight junction structure and function in rats with obstructive jaundice - Ming Zhang; Xiao-Qiong Wang; Yu-Kun Zhou; Yan-Lei Ma; Tong-Yi Shen; Hong-Qi Chen; Zhao-Xin Chu; Huan-Long Qin (Molecular Biology Reports, 2010)

Effects of land cover changes induced by large physical disturbances on hydrological responses in Central Taiwan - Nien Ming Hong; Hone-Jay Chu; Yu-Pin Lin; Dung-Po Deng (Environmental Monitoring and Assessment, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

N2O Emissions under Different Moisture and Temperature Regimes - Han Jian-gang; Zhu Yong-li; Bai Hong-ying; Qu Dong; Chu Jin-yu; Wu Chun-du (Bulletin of Environmental Contamination and Toxicology, 2007)

Mn2 + improves surfactin production by Bacillus subtilis - Yu-Hong Wei; I-Ming Chu (Biotechnology Letters, 2002)